Electrical properties of partially nitrided LiCoO2 thin films with an equivalent amount of Li and Co. (23rd August 2020) - Nagai, Hiroki; Suzuki, Tatsuya; Sato, Mitsunobu
ABSTRACT: Partially nitrided LiCoO2 thin films with stoichiometric contents of Li and Co were fabricated on sapphire substrates using an ethanol solution. The precursor films were formed by spin-coating. By thermal treatment of` the precursor films at 350, 450, 550 and 650°C for 30 min in air, four kinds of LiCoO2 thin films were obtained. That annealing of the precursor film at 650°C resulted in the nucleation of Co3 O4 from the layered LiCoO2, which has been confirmed by the Raman spectrum. Three X-ray photoelectron spectroscopy peaks observed at 527.9 eV, 402.1 eV, and 396.2 eV were newly assigned to the O-Co 4+, N-Co 4+, and N-Co 2+ bonds, respectively, using a peak-analysis technique. The resistivity of the layered LiCoO2 thin film fabricated at 650°C was measured to be 1.2 Ω cm.